(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In Ayurveda, a wide variety of neuroprotective herbal plants have been reported. Brahmi, Bacopa monnieri, belonging to the family Scrophulariaceae, is one of the foremost nootropic and neuroprotective Ayurvedic herb known from ancient times. It is used in the traditional medicinal system to treat various brain related health problems and as a memory enhancer. In the modern era, it is generally used to upgrade memory, learning and to treat tension, depression and other major problems like cardiovascular diseases, gastrointestinal, hepatic, neurological and respiratory problems. There are vast reported studies on the Alzheimer’s disease also, Brahmi is known to have anticancer, antidiabetic, mitigating, antimicrobial and antioxidant properties. Bacopa plants contain various phytochemicals which include alkaloids, flavonoids, glycosides and saponins. Other important constituents present in this plant are bacosides, bacopasides, and bacopa saponins, which are responsible for its therapeutic properties.